RAS pathway targeted therapy in patients with DICER1-associated sarcomas - Lindy Zhang; Paige H. R. Mallinger; Serena Zhou; Stavriani C. Makri; John M. Gross; Calixto-Hope G. Lucas; Ying S. Zou; William Mize; Damon R. Olson; Senna R. Munnikhuysen; Jawhar Rawwas; Yoav Messinger; et al. (npj Precision Oncology)
Abstract DICER1-associated sarcomas commonly exhibit cooperating mutations involving RAS signaling pathways, but the efficacy of therapies that target these mutations is unknown. Here we report two children with DICER1 tumor predisposition who presented with DICER1-associated sarcomas with cooperating, targetable mutations in HRAS or BRAF. Both had relapsed/progressed disease despite upfront multimodal therapy and were subsequently treated with molecularly targeted agents. In the first case, mutant BRAF became amplified after dual dabrafenib/trametinib therapy, presumably as a driver of acquired resistance. In the second case, a subclonal HRAS variant at diagnosis became the predominant clone at autopsy, suggesting its importance in therapy resistance. Together, these two cases provide molecular evidence of the significance of RAS/ERK signaling in DICER1-driven tumorigenesis and highlight the potential for targeting these cooperating mutations.